1996
DOI: 10.1002/(sici)1099-145x(199606)7:2<145::aid-ldr224>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical soil conservation with contour ridges: Cure for, or cause of, rill erosion?

Abstract: Based on the results of an erosion damage assessment in Southern Zimbabwe, where mechanical conservation work has been carried out since the 1940s, this paper describes the impact of mechanical conservation systems on processes leading to rill erosion. In a study of a catchment area, it was found that influxes of water from roads and waterways as well as contour ridges that were originally designed to control rill erosion had a major role in the formation of rills. Existing rills and depressions which cause wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…Widths were measured at several points along a rill and averaged over the rill length (Herweg, 1996). From these measurements, different magnitudes of rill erosion were determined, including rill volumes, rates of erosion, density of rills, area impacted by the rills, and the percentage of area covered by the rills in relation to the total area of surveyed fields (Herweg, 1996;Hagmann, 1996;Bewket and Sterk, 2003). The rill magnitudes were calculated using the following equations:…”
Section: Study Site Descriptionmentioning
confidence: 99%
“…Widths were measured at several points along a rill and averaged over the rill length (Herweg, 1996). From these measurements, different magnitudes of rill erosion were determined, including rill volumes, rates of erosion, density of rills, area impacted by the rills, and the percentage of area covered by the rills in relation to the total area of surveyed fields (Herweg, 1996;Hagmann, 1996;Bewket and Sterk, 2003). The rill magnitudes were calculated using the following equations:…”
Section: Study Site Descriptionmentioning
confidence: 99%
“…The widths and depths of the rill were measured using a measuring tape and a 30 cm ruler respectively, at regular intervals (i.e. 0.01 m) along the sinuous length of the rill, and the averages were calculated (Hagmann, 1996;Sidle et al, 2004).…”
Section: The Measurement Of Rill Dimensionsmentioning
confidence: 99%
“…Sediment discharge from a catchment is highly variable both temporally and spatially (Hagmann, 1996;Yeshaneh et al, 2014;Buendia et al, 2016), which is because the processes driving catchment sediment dynamics have proved to be highly variable in space and time (Liu et al, 2012). Over recent decades, there has been an increased interest in quantifying sediment loads of intra-annual (within a year) variability in addition to inter-annual (between years) in order to improve understanding of suspended sediment loads at a higher temporal resolution (Smith et al, 2003;Seeger et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Over recent decades, there has been an increased interest in quantifying sediment loads of intra-annual (within a year) variability in addition to inter-annual (between years) in order to improve understanding of suspended sediment loads at a higher temporal resolution (Smith et al, 2003;Seeger et al, 2004). This increased interest for intra-annual variability arose because it was shown that for many catchments only a small part of the catchment and only a few heavy rain storms on specific dates produced the bulk of annual sediment yield (Hagmann, 1996;Ziadat & Taimeh, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation